PENYUSUNAN SISTEM AKUNTANSI PENJUALAN KREDIT PADA PT PROBESCO DISATAMA PONTIANAK - B51109062, Edy Riyanto (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
Established companies to seek maximum profits and to maintain its viability. In achieving these goal, the company requires the provision of sufficient information. The role of credit sales accounting system in a business activity is essential to handle the operations of the company to meet the needs for the benefit of management and decision-making. Each accounting system is designed to provide sufficient supervision to ensure all transactions have been recorded, properly authorized, valid, accurate, and able to protect the company's activities are effective and efficient. This research was conducted at PT Probesco Disatama Pontianak. Methods of data collection are observation, interviews, documentation and library research. The technique used is descriptive qualitative nature by describing the facts of that happening are general and possible problems encountered and solution. Results of this study indicate that the accounting system of credit sales at PT Probesco Disatama Pontianak less according to the theory. This is because the PT Probesco Disatama Pontianak in running credit sales system still contained geminating function. The geminating functions contained in the sales department who doubles as the part credit and part warehouse, part concurrently accounting billing section. In addition, there has been no special duty credit function to examine the credit status of customers, so it would allow for doubtful accounts. For documents and accounting records are well used. Advice given is the company should have a separation between the sales and credit department as well as the separation of functions between the accounting and billing section, set the lending standards and credit terms fill out the form and improve the company's organizational structure and needs of its human resources. Keywords : Systems , Accounting , Sales Credit